The Politics of Algorithmic Hyper(in)visibility: BIPOC, LGBTQ+ and Erotic Romance Fiction on Amazon - Parnell, Claire (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2025)
Romance fiction has a complicated relationship with visibility. It is a genre with undeniable presence in the contemporary publishing industry in terms of output and sales, but has historically been hidden in personal, rhetorical, and material ways. Within the genre, BIPOC, LGBTQ+, and erotic romance writers and their works experience a kind of hyper(in)visibility, a concept which describes how non‑normative identities and bodies are overlooked, ignored, and underrepresented, while simultaneously subject to intense scrutiny, surveillance, and stereotyping. Semi‑automated decision‑making technologies, including content moderation and search and recommendation algorithms, further compound these invisibilizing forces. Drawing on interviews with authors, metadata analysis, and critical discourse analysis of terms of service, this article argues that algorithmic systems maintain a politics of hyper(in)visibility for BIPOC, LGBTQ+, and erotic romance authors and books, which risks exacerbation in light of the broader deplatfomization of sex online and current conservative political movements, particularly in the United States.